1997
DOI: 10.1088/0953-4075/30/11/017
|View full text |Cite
|
Sign up to set email alerts
|

Double ionization of neutral atoms, positive and negative ions by electron impact

Abstract: New experimental data on double-ionization cross sections of neutral atoms, positive and negative ions by electron impact are reported. These and other relevant data are compared with recent multiple-ionization semiempirical formulae extended for the case of two-electron ionization. Theory gives analytical dependence of the double-ionization cross sections on the main parameters of the collision system in a wide energy range. For the He atom, He-like ions and H − ion high-energy asymptotic behaviour of the dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 48 publications
(45 reference statements)
1
75
0
Order By: Relevance
“…Shevelko & Tawara (1995a, 1995b) presented a semiempirical formula that describes cross sections for direct multiple ionization of at least three electrons, i.e., triple ionization, from neutral and ionic targets. Bélenger et al (1997) extended their formulae to double ionization. The direct multiple ionization cross sections are approximated by…”
Section: Fitting Formulaementioning
confidence: 99%
“…Shevelko & Tawara (1995a, 1995b) presented a semiempirical formula that describes cross sections for direct multiple ionization of at least three electrons, i.e., triple ionization, from neutral and ionic targets. Bélenger et al (1997) extended their formulae to double ionization. The direct multiple ionization cross sections are approximated by…”
Section: Fitting Formulaementioning
confidence: 99%
“…The double-ionization cross sections ( 0 H À 2 ) for v 3 v 0 , including the additional corrections (Bélenger et al 1997) for the high-energy tail due to distant and close collisions, correspond to experimental high-energy ionization of H À :…”
Section: Double-ionization Rate Of H àmentioning
confidence: 96%
“…However, our theoretical understanding of multi-electron ionization of target systems by electron impact has been hindered by a lack of quantum mechanical calculations, because of many-body correlations in the final channel. Therefore, semiempirical models for multi-electron ionization cross sections have been extensively explored ( Bélenger et al 1997) and compared with experimental results (Shevelko & Tawara 1998). It has been found that the semiempirical Bethe-Born formula (Shevelko & Tawara 1998) reproduces the observed data quite well for most cases.…”
Section: Double Ionization Of H à By Electron Impactmentioning
confidence: 99%
See 2 more Smart Citations